KAJIAN BIOFISIK LAHAN DAN PERFORMANS BISNIS PERTANIAN DATARAN TINGGI DI KABUPATEN KONSERVASI TAMBRAUW PROVINSI PAPUA BARAT - Meky Sagrim; Deny A. Iyai; Stepanus Pakage; Rudolf Tukayo (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2020)
Tambrauw Regency is obliged to safeguard the policies of the central government, especially in food self-sufficiency efforts. Determine locations that have land suitability specifications for soybeans and analyze farming agribusiness as an important factor in agricultural development. The research activity was carried out in Kebar District and Senopi District. Peanut farmers are the focus of research, with the consideration that peanuts and soybeans are a family (leguminoseae). At this stage, the study of the characteristics and specifications of the Kebar District and Senopi District areas as potential areas for the development of soybean commodities was carried out. The study of the shape, pattern, type and pattern of farming, as well as the use of agricultural production facilities by the farming community is carriedout. Data and information from various branches of farming were held with community discussions in the form of FGD. Data analyzed descriptively. The results showed low availability of potassium in flat areas and forests and acidic soil pH in flat-savanna regions. The hindering area is the slope, and flat areas only lack potassium. Potential food crops to be developed are upland rice plants and yams. The results of evaluation of land suitability for horticultural plants (Peanuts, Mustard, Tomatoes and Chillies) show "quite suitable" to "according to the margins". The farming production of Kebar was dominated by agricultural commodities and provides enough income for the household economy.